DEVELOPING MOODLE – BASED INTERACTIVE ONLINE MEDIA TO TEACH NARRATIVE READING IN SMA N 13 SEMARANG - Miftakul Nikmah (Vision: Journal for Language and Foreign Language Learning, 2015)
This research employs research and development model.The conducted development was the interactive online mediabased e-learning of English subject with the Moodle applicationin SMA N 13 Semarang. Moodle (Modular Object-Oriented Dy-namic Learning Environment) is a course management system foronline learning using PHP and MySQL. The learning instrumentdevelopment design was carried out using the six steps of Borgand Gall model. They were need analysis, planning, developingpreliminary Moodle-based interactive online media, preliminaryfi eld testing, Moodle-based interactive online media revision, andmain fi eld testing. The data collecting techniques used in this re-search were interview, questionnaire and documentation. The de-veloping result of interactive online media Moodle-based to teachnarrative reading could be accessed at http://www.elen.airybelle.com.